A Response to Widening Participation in Medicine: The Impact of Medical Student-Led Conferences for Year 12 Pupils [Letter] - Matos Lopes De Campos F; Clementson K (Advances in Medical Education and Practice, 2021)
Filipa Matos Lopes De Campos, Katie Clementson Faculty of Medicine, Department of Medicine, Imperial College London, London, UKCorrespondence: Filipa Matos Lopes De Campos Email filipacampos998@gmail.com View the original paper by Dr Ryan and colleagues